Textual and pictorial representations in strategic thinking about linguistic meaning - Šarčanin, Marta (Array, 2019)
The aim of this study was to investigate L2 speakers’ ability to think strategically about linguistic meaning by asking them to make sense of particle verb (PV) constructions, a particularly demanding aspect of the English language for L2 speakers. Our focus was on meaning construal strategies in textual and pictorial representations of 22 figurative PVs with the particle down. The participants were asked to express themselves verbally and visually, and we were interested in the nature of their answers as well as their relationship. More specifically, we wished to determine the salience of particular elements in the participants’ strategic meaning construal, the type of relationship between textual and pictorial representations and, finally, potential dominance of one mode over another, which was examined in terms of the well-established concepts of “relay” and “anchorage”. The results showed that participants generally related the meaning of the PV construction to its components in their textual answers, whereas in pictorial answers their main tendency was to attend to the figurative meaning of the PV. Furthermore, their textual and pictorial answers most frequently depended on each other, which allowed us to determine that the text-picture relationship was predominantly that of relay, i.e. that text was perceived as more significant in the text-picture relationship.